Perancangan dan Implementasi Sistem Pendataan Kasus Tindak Pidana - Ryan Aji Wijaya; Angga Dri Hananto; Adimas Rexsi Saputra (LPPM Universitas Muhammadiyah Kotabumi, 2022)
North Lampung Police has a vision of realizing a professional, moral, modern, superior and trustworthy Police Police of North Lampung in order to support the creation of a sovereign, independent and personable Indonesia based on mutual cooperation. And to realize this vision, the North Lampung Police have several missions, one of which is to realize the sustainable use of technology and police data systems that are integrated in the North Lampung Police Station area, which is supported by scientific studies and studies, in order to further optimize the performance of the Police. Based on the results of the competition above, the researcher won 3rd place with the title